The POSEIDON Criteria and Its Measure of Success Through the Eyes of Clinicians and Embryologists - Esteves, Sandro C.; Alviggi, Carlo; Humaidan, Peter; Fischer, Robert; Andersen, Claus Y.; Conforti, Alessandro; Bühler, Klaus; Sunkara, Sesh K.; Polyzos, Nikolaos P.; Galliano, Daniela; Grynberg, Michael; Yarali, Hakan; et al. (Frontiers in Endocrinology, 2019)
This article represents a perspective viewpoint on the POSEIDON criteria by a group of clinicians and embryologists. Its primary objective is to serve as a perspective summary for the relevant Frontiers research topic “POSEIDON’s Stratification of ‘Low Prognosis Patients in ART”. ‘Low prognosis’ relates with reduced oocyte number, which can be associated with low or sometimes a normal ovarian reserve and is aggravated by advanced female age. These aspects will ultimately affect the number of embryos generated and consequently, the cumulative live birth rate. The novel system relies on female age, ovarian reserve markers, ovarian sensitivity to exogenous gonadotropin, and the number of oocytes retrieved, which will both identify the patients with low prognosis and stratify such patients into one of four groups of women with “expected” or “unexpected” impaired ovarian response to appropriate exogenous gonadotropin stimulation. Furthermore, the POSEIDON group introduced a new measure of clinical success in ART, namely, the number of oocytes needed to obtain at least one euploid blastocyst for transfer in each patient. Using the POSEIDON criteria, the clinician would firstly identify and classify patients who have low prognosis in ART, and secondly, aim at designing an individualized treatment plan to maximize the chances of achieving the POSEIDON measure of success in each of the four low prognosis groups. The novel POSEIDON classification system is anticipated to improve counseling and management of low prognosis patients undergoing ART, with an expected positive effect on reproductive success and a reduction in time to live birth.